Pertanggung Jawaban Pidana Pelaku Pemerkosaan Anak Oleh Ayah Kandung - Dimas Aditya Wahyu Pratama; Hartoyo .; Moh. Taufik (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
The crime of raping a child committed by a biological father is a form of sexual violence that is very concerning and has become a deep social and legal problem. This article aims to analyze the criminal liability of perpetrators of child rape by the biological father, by highlighting various aspects of Indonesian criminal law, child protection law, and the role of psychology in exploring the factors that encourage this criminal act. The method used in this research is a qualitative approach with literature study and in-depth interviews with sources consisting of legal practitioners and forensic psychology experts. The results of the research show that perpetrators of child rape by the biological father can be charged with various articles in the Criminal Code (KUHP), including articles on rape and sexual violence against children, as well as factors that aggravate the consequences of family relationships. This article also recommends the need for a multidisciplinary approach in handling this case, including preventive efforts involving the family, community and state.